Phase-Field Modelling of Bimodal Dendritic Solidification During Al Alloy Die Casting - Maryam Torfeh; Zhichao Niu; Hamid Assadi (Metals)
Tracking the microstructural evolution during high-pressure die casting of Al-Si alloys is challenging due to the rapid solidification, varying thermal conditions, and severe turbulence. The process involves a transition from slower cooling in the shot sleeve to rapid cooling in the die cavity, resulting in a bimodal dendritic microstructure and nucleation of new finer dendrite arms on fragmented externally solidified crystals. In this study, a two-dimensional phase-field model was employed to investigate the solidification behaviour of a hypoeutectic Al-7% Si alloy during high-pressure die casting. The model is based on thermodynamic formulations that account for temperature changes due to phase transformation heat, thermal boundary conditions, and solute diffusion in both liquid and solid phases. To replicate the observed bimodal microstructure, solid–liquid interface properties such as thickness, energy, and mobility were systematically varied to reflect the transition from the shot sleeve to the die cavity. The results demonstrated the model’s ability to capture the growth of dendrites under shot sleeve conditions and nucleation and development of new dendrite arms under the rapid cooling conditions of the die cavity.